Effect of Mixing Methods and Black Conductive Fillers on Properties of Natural Rubber Composites - Bhatt, Anal; Mahadwad, Omprakash; Parikh, Parimal (Journal of Research Updates in Polymer Science, 2024)
Carbon black, graphite, carbon nanofibers, carbon nanotubes, and metal fillers increase composite conductivity in natural rubber, which is electrically insulating. Depending on dispersion, conductive filler lowers insulating material resistivity. These materials are frequently used for electromagnetic/radio frequency interference (EMI/RFI) shielding, conductive flexible seals gaskets, and conductive mats used to prevent electrostatic damage to electronic devices. These elastomers could be used to make flexible solar cells or mechanical-to-electricity devices. Temperature, mixing time, shear rate, and cross-linking during vulcanization affect rubber electrical conductivity of composite. To study shear rate effects, vulcanizate of Natural Rubber-based composites filled with carbon black, millable carbon fiber powder, and synthetic graphite powder was prepared by open mixing (two roll mill) and close mixing (internal mixer). We compared how shear rate affects cure, stress-strain, and volume resistivity of conductive filler-based Natural Rubber composites. Increment in clearance of two roll mill during addition of rubber additives along with rubber of reduced the shearing force resulted in less dispersive and distributive mixing and stagnant points due to band formation on roll surface compared to intermix where compound movement had no stagnation point and long wings pushed material axially and two nogs pushed material in other chamber. Compared to two roll mill samples, the compound reached every point of the mixing chamber for best homogeneity, reducing cure time and improving stress-strain and volume resistivity.